The effect of a structured physical exercise program on the psychological well-being of the elderly in nursing homes - Ariyanti, Sri; Cahyono, Didik; Sima, Yenny; Pannyiwi, Rahmat; Masdarwati, Masdarwati (Journal of Midwifery and Nursing, 2024)
Structured physical exercise programs can have a significant influence on the psychological well-being of older people in nursing homes. Research shows that by designing an exercise program tailored to individual health conditions and needs, such as in consultation with a fitness professional or physiotherapist, older adults can reap multiple benefits, including improved mental health, enhanced emotional well-being and improved sleep. These programs can also help to increase the independence of older adults and reduce the risk of depression and other mental illnesses. However, the implementation of structured physical exercise programs in nursing homes can face challenges such as limited resources, individual health challenges, and lack of knowledge and awareness about the benefits of physical activity. Overcoming this requires a holistic approach that involves various parties, including nursing home staff, fitness experts, and the families of the elderly. With tailored program development and careful supervision, physical exercise programs can be an effective tool in improving the physical and psychological well-being of older adults in nursing homes.